Financial Statement Complexity and Bank Lending - Chakraborty, Indraneel; Leone, Andrew J.; Minutti-Meza, Miguel; Phillips, Matthew A. (The Accounting Review, 2022)
ABSTRACT Recent evidence suggests that investors struggle to process complex financial disclosures. Relative to equity and public debt investors, banks have unique advantages in acquiring information and can impose contractual terms to mitigate information frictions. We investigate whether financial statement complexity is associated with firms' reliance on bank financing and the terms of bank loans. We focus on two aspects of complexity: the length of financial reports and the complexity of financial reporting rules. We document that both aspects of complexity are positively associated with firms' reliance on bank financing (i.e., level of debt and new financing). This result is consistent with banks' superior information processing capabilities. Next, we document that banks ameliorate information frictions using loan contractual terms that depend on the source of complexity. Overall, banks are an attractive source of financing for firms with complex disclosures, but banks also increase screening and monitoring for relatively complex borrowers. Data Availability: Data used in this study are available from public sources identified in the study. JEL Classifications: M41; G14; G21; G32; D82.